With or without emoji?: impact of the use of emojis on online service booking on consumer perception - Xavier, Sílvia Cristina do Carmo (2019)
With the evolution of technology, we are currently experiencing a period in which communication is often mediated by computers (CMC). In addition to using this mode of communication between friends and colleagues, there are many pages and more and more services and brands to evolve into social networks. For example, there is even and the possibility of booking services through these methods (Facebook chat). With these new forms of communication existed, the language also changes. There was thus a need to adapt this new way of communicating the need to include non-verbal cues that are common in face-to-face communication (F2F). This is how emoticons and emoji came about. We carried out an experimental study to investigate how the use of emoji can influence consumers' perception of online services (Facebook chat) and restaurant. Participants (N = 200, 74% female) were exposed to a fictitious scenario that represented a negative or positive message (e.g., reservation request refused vs. accepted) and which included or not emoji was distinct in the presence or absence of emoji and in the valence of the message congruent with this message. The results indicate that the emoji exert influence in the perception of the consumers about the service and the restaurant, at several levels such as: the perception of modernity, the language used and the warmth. These evidences denote importance for the psychology of the consumer, because they indicate how much emoji can influence the consumer to have different perceptions about services used and brands.